Difference Between Young and Old Adults' Performance on the Psychology Experiment Building Language (PEBL) Test Battery: What Is the Role of Familiarity With Technology in Cognitive Performance?. (September 2021) - Scarpina, Federica; D'Agata, Federico; Priano, Lorenzo; Mauro, Alessandro
Objective: The Psychology Experiment Building Language (PEBL) Test Battery is a recent computerized software for the assessment of cognitive functioning in clinical and healthy populations. However, its applicability for the assessment of old adults and the role of level of familiarity with technology on performance have not been tested.Method: To verify if PEBL Test Battery is sensitive to aging cognitive decline, we assessed young and older adults' performance on the neuropsychological tests relative to the following domains: verbal and visuospatial short-term memory, selective attention, inhibition to interference, planning and problem-solving, set-shifting, and cognitive flexibility. The difference between the two groups was studied taking into account the self-reported level of familiarity with technology, measured through the Attitudes Toward Computers Questionnaire.Results: Old participants showed a lower level of cognitive performance compared with the younger group, in line with the traditional literature about cognitive function decline in aging. However, this difference was not related to the level of familiarity with technology.Conclusion: Our descriptive study seemed to support the applicability of PEBL Test Battery for testing old adults' cognitive functioning. However, some criticisms and future improvements about this computerized battery were discussed for its applicability in clinical, rehabilitative and research contexts.